'Celebrating diverse motherhood': physically disabled women's counter-narratives to their stigmatised identity as mothers. (30th November 2018) - Lappeteläinen, Anita; Sevón, Eija; Vehkakoski, Tanja
Abstract : This study examined how disabled women negotiated their stigmatised identity as mothers by presenting counter-narratives to the culturally dominant narrative of disabled motherhood. Eleven Finnish physically disabled mothers were interviewed. The data were analysed by focusing on these counter-narratives, their linguistic features and their functions in the interviews. The disabled mothers produced four types of counter-narratives about their motherhood experiences: (1) celebrating diverse motherhood through individual coping; (2) performing motherhood through collaborative caring; (3) boosting motherhood through praising one's children; and (4) normalising (disabled women's) motherhood through identifying with the mother community. All the counternarratives included explicit or implicit references to the culturally dominant narratives of disabled motherhood, but instead of taking their stigmatised identity for granted, they adopted a critical position towards it. Producing counter-narratives enabled the disabled mothers to position themselves as good mothers and care providers, and not as questionable mothers or recipients of care.